2012
DOI: 10.1080/14616734.2012.727255
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational relations of attachment: a research synthesis of urban/rural Mexican samples

Abstract: Intergenerational relations of attachment, including adult state of mind, adult care giving quality, and infant behavior, were examined in urban and rural samples. The sample included 66 dyads of contrasting populations, 35 middle-high urban Spanish speaking families and 31 rural Indian peasant families. Measures included the Adult Attachment Interview (George, Kaplan, & Main, 1985 /1996), home observations of mother-infant, and the Strange Situation attachment assessment (Ainsworth, Blehar, Waters, & Wall, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…These finding were also detected by another study conducted in Chinese families (36). In addition, studies have shown that parents living in urban region pay more attention to adolescents' daily lifestyle (37). A stronger relationship between mothers and daughters had been detected, and this observation was in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…These finding were also detected by another study conducted in Chinese families (36). In addition, studies have shown that parents living in urban region pay more attention to adolescents' daily lifestyle (37). A stronger relationship between mothers and daughters had been detected, and this observation was in agreement with previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, Mary Ainsworth's first descriptions of behaviors that reflect sensitive responsiveness were based on her observations in Uganda (Ainsworth, 1967). Cross-cultural research indeed confirms that sensitivity and attachment can be validly measured in nonWestern contexts, and also relates to secure infant attachment in the expected directions in countries such as China (Ding, Xiu, Wang, Li, & Wang, 2012), Japan (Vereijken, Riksen-Walraven, & Kondo-Ikemura, 1997), South Korea (Jin, Jacobvitz, Hazen, & Jung, 2012), Mali (True, Pisani, & Oumar, 2001), Mexico (Gojman et al, 2012), and South Africa (Tomlinson, Cooper, & Murray, 2005). Further, some of the main components of sensitivity represent universally important aspects of caregiving.…”
mentioning
confidence: 77%
“…In fact between‐individual variations in the level of sensitive responsiveness have been reported by Ainsworth in her Uganda study (). Others have shown that sensitivity in non‐Western contexts relates meaningfully to infant development including attachment security (e.g., Gojman et al., ; True et al., ) as well as to maternal characteristics also found to be associated with variations in sensitivity such as the quality of maternal education (Valenzuela, ), depression and partner support (Tomlinson et al., ), and maternal attachment representations (Gojman et al., ). These findings provide evidence for the validity of the sensitivity construct in non‐Western cultures.…”
Section: Discussionmentioning
confidence: 99%
“…In a study among the Dogon in Mali, maternal sensitivity observed during 30 min of daily routines was marginally related to secure attachment (True, Pisani, & Oumar, ). Sensitivity during daily routines was also related to infant secure attachment in rural and urban Mexico (Gojman et al., ). Sensitivity as observed in more brief and standardized settings has been shown to be associated with secure attachment in samples from urban South Africa (Tomlinson, Cooper, & Murray, ), urban Colombia (Posada et al., ), urban South Korea (Jin, Jacobvitz, Hazen, & Jung, ), and urban Japan (Vereijken, ).…”
Section: The Attachment Theory Perspectivementioning
confidence: 99%